PENGARUH KEPEMILIKAN INSTITUSIONAL, CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2016-2018 - Thania, Sastra Tamara; Vince, Ratnawati; Nanda, Fito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the influence of institutional ownership, capital intensity and inventory intensity to tax aggressiveness on manufacturing companies listed on the Indonesia Stock Exchange period 2016-2018. This type of research is quantitative. The sample consisted of 56 companies. Sampling technique with purposive sampling technique. Hypothesis testing in this study using multiple linear regression analysis method with SPSS program. The result of the study show that, (1) institutional ownership had no effect on tax aggressiveness (2) capital intensity has a positive effect on tax aggressiveness (3) inventory intensity had no effect on tax aggressiveness.Keywords : Institutional Ownership, Capital Intensity, Inventory Intensity and Tax Aggressiveness